ORGANIZATIONAL ASPECTS OF THE REGULATIONS AND ORGANIZATIONSACTIVITIES OF THE CUSTOMS UNION COMMISSION (Journal of actual problems of jurisprudence, 2019)
R. Alimkulov’s article provides an overview and legal aspects of making organ of the Eurasian Economic Community (EEC)concerning the functioning of the Customs Union.